PERAN BK DALAM IDENTIFIKASI KEBUTUHAN DAN MASALAH SISWA (IKMS) UNTUK MENINGKATKAN HASIL BELAJAR: IKMS, Peran BK, motivasi belajar - Wachid Hadicahyono (Psikologi Prima, 2020)
Identification of student needs and problems is one of the instruments used in this study. The aims and objectives of this study were a response to the decline in student motivation at SMAN 1 Pagaden. The author as a counseling teacher collaborates with the homeroom teacher and subject teacher to find a formulation that can increase student motivation again. Furthermore, this study is an effort to improve student learning outcomes in Class X IPS 2 which is based on statistics among other class X IPS, on average, students experience difficulties in learning. This can be seen from the achievement of scores where many students get scores below the KKM (Minimum Completeness criteria). Based on the results of the analysis of the identification of student needs and problems (IKMS), it was found that the lack of student motivation in Class X IPS 2 was caused by experiencing saturation with the monotonous teaching style of the teacher. These findings become recommendations to class X IPS 2 class teachers and subject teachers to change teaching styles. Different situations in the learning process actually provide a very significant increase in learning outcomes from around 57% to 84%. This research is expected to become a model of cooperation between subject teachers in order to produce integrated learning